Analysis Of The Condition Of Aviation Security Work Unit (Avsec) Equipment In Supporting Aviation Security And Safety At Yogyakarta Adisutjipto Airport - Bhernica Irnadianis Ivada; Kartika Fajar Nieamah (Formosa Journal of Science and Technology, 2023)
Currently, many crimes have been found at airports, such as smuggling of illegal drugs, sharp weapons or other dangerous goods. Therefore, aviation security and safety must be met and considered by the Aviation Security (AVSEC) work unit. This study aims to explain the application of AVSEC security inspection procedures and the condition of the equipment. The results of the study showed that the application of the AVSEC security inspection procedure was not maximized. This is caused by the equipment in the AVSEC unit which is still experiencing problems such as the HHMD experiencing a low battery resulting in a less loud metal ticking sound. The WTMD engine that is experiencing problems does not sound when checking passengers carrying metal-containing goods. X-ray machines that experience problems due to cables that don't fit properly result in the X-ray machine not being able to see images of items that go through the X-ray machine during inspection. So that it can hinder the process of security checks at Yogyakarta Adisutjipto airport.